The Aftermath of Covid-19 Pandemic on the Operation of SMEs in Yobe State, Nigeria: The Role of Islamic Finance Models - Muhammad Duku (Al-bank: Journal of Islamic Banking and Finance, 2026)
This study examines the post-COVID-19 operational challenges faced by Small and Medium Enterprises (SMEs) in Yobe State, Nigeria, and explores Islamic finance models as potential mechanisms for recovery and sustainability. Employing a qualitative descriptive approach, primary data were collected through structured field observations of selected SME operators across key economic sectors. The findings reveal that limited access to capital, shortage of skilled personnel, multiple taxation, inadequate raw materials, and heightened insecurity remain the major constraints hindering SME operations in the post-pandemic period. The study further argues that Islamic finance instruments—such as Musharakah, Mudarabah, Murabahah, Ijarah, Salam, and Istisna‘—offer viable, ethical, and risk-sharing financing alternatives capable of addressing these challenges. The paper contributes to the growing literature on Islamic social and commercial finance by providing contextual evidence from a conflict-affected and economically disadvantaged region. Policy recommendations emphasize the need for increased Islamic finance awareness, regulatory support, and the integration of Islamic banking products into SME development strategies in Nigeria